Surface Chemistry and Catalysis (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Summary/Description for Distribution Channels: The present printed edition of the Special Issue "Surface Chemistry and Catalysis" published in Catalysts aims to cover some of the recent advances in the field of heterogeneous catalysis that can be obtained by means of advanced characterization techniques, computational calculations and time-resolved methods, with particular emphasis on structure-activity relationships (SARs). It consists of 14 high-quality theoretical and experimental studies on various aspects on catalysis, involving the electrochemical promotion in catalysis, H2O dissociation, H2 production, Fisher-Tropsch synthesis, CO oxidation, among others.